Essence of the patterns of cover and richness of intertidal hard bottom communities: a pan-European study. (4th October 2016) - Kotta, Jonne; Orav-Kotta, Helen; Jänes, Holger; Hummel, Herman; Arvanitidis, Christos; Van Avesaath, Pim; Bachelet, Guy; Benedetti-Cecchi, Lisandro; Bojanić, Natalia; Como, Serena; Coppa, Stefania; Coughlan, Jennifer; et al.
Abstract : Coastal ecosystems are highly complex and driven by multiple environmental factors. To date we lack scientific evidence for the relative contribution of natural and anthropogenic drivers for the majority of marine habitats in order to adequately assess the role of different stressors across the European seas. Such relationship can be investigated by analysing the correlation between environmental variables and biotic patterns in multivariate space and taking into account non-linearities. Within the framework of the EMBOS (European Marine Biodiversity Observatory System) programme, hard bottom intertidal communities were sampled in a standardized way across European seas. Links between key natural and anthropogenic drivers and hard bottom communities were analysed using Boosted Regression Trees modelling. The study identified strong interregional variability and showed that patterns of hard bottom macroalgal and invertebrate communities were primarily a function of tidal regime, nutrient loading and water temperature (anomalies). The strength and shape of functional form relationships varied widely however among types of organisms (understorey algae composing mostly filamentous species, canopy-forming algae or sessile invertebrates) and aggregated community variables (cover or richness). Tidal regime significantly modulated the effect of nutrient load on the cover and richness of understorey algae and sessile invertebrates. In contrast, hydroclimate was more important for canopy algae and temperature anomalies and hydroclimate separately or interactively contributed to the observed patterns. The analyses also suggested that climate-induced shifts in weather patterns may result in the loss of algal richness and thereby in the loss of functional diversity in European hard bottom intertidal areas.